Processing of increased frequency of social interaction in social anxiety disorder and borderline personality disorder - Anna Weinbrecht (Nature Portfolio, 2021)
Abstract We investigated how patients with social anxiety disorder (SAD) and patients with borderline personality disorder (BPD) process an increase in the frequency of social interaction. We used an EEG-compatible version of the online ball-tossing game Cyberball to induce an increase in the frequency of social interaction. In the first condition, each player received the ball equally often (inclusion: 33% ball reception). In the following condition, the frequency of the ball reception was increased (overinclusion: 45% ball reception). The main outcome variable was the event-related potential P2, an indicator for social reward processing. Moreover, positive emotions were assessed. Twenty-eight patients with SAD, 29 patients with BPD and 28 healthy controls (HCs) participated. As expected, HCs and patients with BPD, but not patients with SAD, showed an increase in the P2 amplitude from the inclusion to the overinclusion condition. Contrary to our expectations, positive emotions did not change from the inclusion to the overinclusion condition. EEG results provide preliminary evidence that patients with BPD and HCs, but not patients with SAD, process an increase in the frequency of social interaction as rewarding.